2022
DOI: 10.1186/s12909-022-03115-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining the influence of different linking patterns on the stability of students’ score adjustments produced using Video-based Examiner Score Comparison and Adjustment (VESCA)

Abstract: Background Ensuring equivalence of examiners’ judgements across different groups of examiners is a priority for large scale performance assessments in clinical education, both to enhance fairness and reassure the public. This study extends insight into an innovation called Video-based Examiner Score Comparison and Adjustment (VESCA) which uses video scoring to link otherwise unlinked groups of examiners. This linkage enables comparison of the influence of different examiner-groups within a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several parameters could conceivably in uence the accuracy of score estimates produced by VESCA. As Yeates et al (17)have previously shown that rstly examiner participation rates and secondly the number of linking videos scored by each examiner can both in uence score adjustments, both these variables seem germane to understanding VESCA's accuracy. Theoretically, we would expect that with greater amounts of linking material (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several parameters could conceivably in uence the accuracy of score estimates produced by VESCA. As Yeates et al (17)have previously shown that rstly examiner participation rates and secondly the number of linking videos scored by each examiner can both in uence score adjustments, both these variables seem germane to understanding VESCA's accuracy. Theoretically, we would expect that with greater amounts of linking material (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Critically, as the authors acknowledge in each paper, these observations depend on a strong assumption that the adjusted scores produced by VESCA (generally through Many Facet Rasch Measurement) are indeed more accurate representations of candidates' true performance than their raw scores. Yeates et al (17) used subset resampling from Yeates 2021 data to explore this potential. By varying the number of linking videos per participating examiner and the proportion of examiners who scored videos, they showed that candidates' score adjustments (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up work has enhanced the technique’s feasibility, 24 and shown that it is adequately robust to several potential confounding influences 25 and variations in implementation. 26 While these findings suggest that examiner-cohort effects are important and support the validity of VESCA for their measurement, VESCA has not yet been used across institutions, so both the likely magnitude of effects which may arise, and the practical implications of applying the method across institutions are unknown.…”
Section: Introductionmentioning
confidence: 99%